Portable single port 23-gauge vitrectomy in postoperative endophthalmitis - Höhn, Fabian (Clin Ophthalmol, 2015)
AIM: To evaluate the safety and effectiveness of the Intrector(®) for treating postoperative endophthalmitis. MATERIALS AND METHODS: In a retrospective multicenter study, patients who received a single port 23-gauge core pars plana vitrectomy and isovolumetric injection of vancomycin, ceftazidime, and dexamethasone/amphotericin B using the Intrector(®) for postoperative endophthalmitis of intermediate severity (grade II or III vitreous inflammation and best-corrected visual acuity between hand movements and 0.3 logMAR [logarithm of the minimum angle of resolution]) were evaluated. Improvement in visual acuity, resolution of intraocular inflammation, the need for additional surgical procedures, and the development of complications were evaluated at a 1-month follow-up examination. RESULTS: Fifteen patients (mean age 55.6±7.2 years) underwent treatment with the Intrector(®). The mean vitreous volume aspirated was 0.78±0.22 mL. The vitreous samples indicated positive microorganism culture results in six of the 15 cases, but the samples were positive when analyzed by real-time polymerase chain reaction in all cases (15/15). The mean best-corrected visual acuity improved significantly (P=0.01) from 0.88±0.29 (logMAR) to 0.32±0.28. Each patient demonstrated at least three lines of visual improvement. No additional medical or surgical interventions were required, and the complete resolution of intraocular inflammation was noted in all patients at the 1-month follow-up examination. No procedure-related complications were observed. CONCLUSION: The Intrector(®) may be a safe and effective treatment option for infectious postoperative endophthalmitis. Larger studies comparing the outcomes of the Intrector(®) to the traditional treatments for postoperative endophthalmitis need to be conducted before its role in the treatment of postoperative endophthalmitis can be properly defined.